Posterior parietal cortex dynamically ranks topographic signals via cholinergic influence - Broussard, John (Frontiers in Integrative Neuroscience, 2012)
The hypothesis to be discussed in this review is that posterior parietal cortex is directly involved in selecting relevant stimuli and filtering irrelevant distractors. The posterior parietal cortex receives input from several sensory modalities and integrates them in part to direct the allocation of resources to optimize gains. In conjunction with prefrontal cortex, nucleus accumbens, and basal forebrain cholinergic nuclei, it comprises a network mediating sustained attentional performance. Numerous anatomical, neurophysiological, and lesion studies have substantiated the notion that the basic functions of the posterior parietal cortex are conserved from rodents to humans. One such function is the detection and selection of relevant stimuli necessary for making optimal choices or responses. The issues to be addressed here are how behaviorally relevant targets recruit oscillatory potentials and spiking activity of posterior parietal neurons compared to similar yet irrelevant stimuli. Further, the influence of cortical cholinergic input to posterior parietal cortex in learning and decision-making is also discussed. I propose that these neurophysiological correlates of attention are transmitted to frontal cortical areas contributing to the top down selection of stimuli in a timely manner.